A nationwide study of maternal exposure to ambient ozone and term birth weight in the United States. (December 2022) - Sun, Shengzhi; Wang, Jiajia; Cao, Wangnan; Wu, Lizhi; Tian, Yu; Sun, Feng; Zhang, Zhenyu; Ge, Yang; Du, Jianqiang; Li, Xiaobo; Chen, Rui
Graphical abstract: Highlights: We estimated the association of O3 exposure with fetal growth across 453 US counties. Maternal exposure to O3 was associated with reduced birth weight. Maternal exposure to O3 was associated with a higher risk of SGA. The 13th-25th gestational weeks were the identified critical exposure windows. Abstract: Background: Maternal exposure to ozone (O3 ) may cause systemic inflammation and oxidative stress and contribute to fetal growth restriction. We sought to estimate the association between maternal exposure to O3 and term birth weight and term small for gestational age (SGA) in the United States (US). Methods: We conducted a nationwide study including 2, 179, 040 live term singleton births that occurred across 453 populous counties in the contiguous US in 2002. Daily county-level concentrations of O3 data were estimated using a Bayesian fusion model. We used linear regression to estimate the association between O3 exposure and term birth weight and logistic regression to estimate the association between O3 exposure and term SGA during each trimester of the pregnancy and the entire pregnancy after adjusting for maternal characteristics, infant sex, season of conception, ambient temperature, county poverty rate, and census region. We additionally used distributed lag models to identify the critical exposure windows by estimating the monthly and weekly associations. Results: A 10 parts per billion (ppb) increase in O3 over the entire pregnancy was associated with a lower term birth weight (-7.6 g; 95 % CI: −8.8 g, −6.4 g) and increased risk of SGA (odds ratio = 1.030; 95 % CI: 1.020, 1.040). The identified critical exposure windows were the 13th- 25th and 32nd −37th gestational weeks for term birth weight and 13th- 25th for term SGA. We found the association was more pronounced among mothers who were non-Hispanic Black, unmarried, or had lower education level. Conclusions: Among US singleton term births, maternal exposure to O3 was associated with lower rates of fetal growth, and the 13th- 25th gestational weeks were the identified critical exposure windows.